GLUCOSE AND CHOLESTEROL SCREENING IN THE ELDERLY IN THE WORKING AREA OF THE SRIKUNCORO HEALTH CENTER, CENTRAL BENGKULU DISTRICT, 2024 - Putri W. Welkriana; Jon Farizal; Heru Laksono (Bajang Institute, 2024)
Health screening of the elderly is an important endeavor to improve quality of life and life expectancy. The rise of chronic diseases among the elderly is attracting public health attention due to the increasing proportion of the elderly population. Conditions such as hypertension, diabetes mellitus, stroke, cardiovascular disease, and cancer, are the leading causes of death worldwide. Periodic health check-ups are an attempt to reduce or control the severity of these chronic diseases in older people. Community-based health interventions are needed to raise awareness to increase the frequency of visits to health services, such as posyandu lansia. The purpose of this community service activity is to check glucose, cholesterol, and blood pressure in the elderly in the Srikuncoro Health Center Working Area. This activity was carried out in collaboration with the Medical Laboratory Technology Study Program, Department of Health Analysts, Poltekkes Kemenkes Bengkulu with the Central Bengkulu Regency Government, especially the Srikuncoro Health Center Working Area. Based on the results of IDF (2019) the number of people with Diabetes Mellitus (DM) in the world is still high, which is 467 million, while in Southeast Asia the prevalence of DM is 11.3%. The incidence rate in Indonesia is 10.7%. The incidence of DM in Bengkulu is 48%. This community service is carried out to screen the elderly community to check glucose, cholesterol, and blood pressure as an effort to prevent the occurrence of non-communicable diseases that are at risk in the elderly